Burden of stroke in adolescents and young adults (aged 15–39 years) in South East Asia: a trend analysis from 1990 to 2021 based on the global burden of disease study 2021 - Satapathy, Prakasini; Chauhan, Shubham; Gaidhane, Shilpa; Bishoyi, Ashok Kumar; Priya, G. Padma; Jayabalan, Karthikeyan; Mishra, Swati; Sharma, Shilpa; Bushi, Ganesh; Shabil, Muhammed; Syed, Rukshar; Kundra, Kamal; et al. (Frontiers in Stroke, 2025)
BackgroundStroke is a leading cause of morbidity and mortality globally, yet its burden among adolescents and young adults (aged 15–39 years) in South East Asia (SEA) remains understudied. Understanding regional trends and risk factors in this population is critical for effective prevention and management strategies. This study aims to examine stroke trends from 1990 to 2021, focusing on ischemic stroke, intracerebral hemorrhage (ICH), and subarachnoid hemorrhage (SAH) in SEA.MethodsUsing data from the Global Burden of Disease (GBD) 2021 study, temporal trends in stroke incidence, mortality, and Disability-Adjusted Life Years (DALYs) were analyzed for the age group 15–39 years. Join point regression analysis was employed to identify significant changes in stroke trends, and gender specific patterns were also assessed.ResultsIschemic stroke cases in SEA increased from 28030.85 to 40836.18, with a slight rise in incidence, particularly affecting males aged 30–39, while female mortality dropped by 23.81%. ICH incidence decreased annually by 0.6692%, with significant reductions in DALYs and mortality, especially among younger age groups and females. SAH incidence declined by 0.2142%, accompanied by a notable reduction in female mortality (31.83%). Countries with lower SDI experienced higher stroke incidence and mortality rates, highlighting socio-economic disparities. Geographic analysis revealed the Philippines had the highest rise in ischemic stroke, while most other countries saw declines in ICH and SAH rates.ConclusionThe study highlights significant progress in managing ICH and SAH, especially among younger populations and females. However, ischemic stroke remains a growing challenge, particularly for males, necessitating targeted interventions to reduce the overall stroke burden.